Hunger and torture.: Assessing the adequacy of prison food under international law - Cakal, Ergun (Torture Journal, 2022)
Background: Deprivation of prisoner food, in terms of its quality and quantity, has generally been accepted as violating the prohibition as torture and ill-treatment, particularly when combined with other factors (ie. harmful conditions and methods). Aspects relevant to assessing when and how food provision is considered inadequate, however, remain complex and confusing. This article presents a doctrinal review which consolidates normative understandings of adequate prisoner food. Method: A systematic full-text search was made of international and regional normative standards, case-law and commentary using the keywords. These were then selected based on their relevance for regulatory and explanatory specificity and pertinence to detention contexts. Findings: International and regional bodies directly connect the adequacy of food to respect for dignity, freedom from torture and ill-treatment as well as the right to health – and particularly as depending on duration, quality, quantity and variety. What constitutes inadequate food remains complex as it is contingent on both material and non-material considerations, including its quality (content, nutritiousness, edibility, variety, wholesomeness), its quantity (calorie, substantiveness, balance), its preparation (hygiene, respect to the individual and community), its provision and consumption (when, how and where it is to be eaten, regularity, accessibility, warmth/cold), its socio-cultural suitability (to religious and cultural values) and its developmental suitability (for pregnant or breast-feeding mothers and children).